Characterization of Pollinators Associated with Cocoa Cultivation and Their Relationship with Natural Effective Pollination - Ríos Moyano, Diana Katherinne; Rodríguez Cruz, Fredy Alexander; Hormaza Martínez, Paola Andrea; Ramírez Godoy, Augusto (Multidisciplinary Digital Publishing Institute - MDPI, 2025)
Cocoa (Theobroma cacao L.) relies on insect pollination for fruit production, making it essential to understand the pollinators involved. This study aimed to identify the insects associated with cocoa pollination and their relationship with effective natural pollination in a cocoa agroforestry system in Yopal, Colombia. Indirect (wood traps) and direct (manual aspiration in flowers) methods were used to capture pollinators. The number of captured insects was correlated with the percentage of pollinated, fertilized, aborted, and transitioning flowers using Pearson’s correlation coefficient. Additionally, the natural transfer of pollen was assessed by evaluating the coverage of near-opening flowers and staining pollen grains on the stigma under natural conditions. This study identified Diptera from the Ceratopogonidae family, specifically the genera Forcipomyia and Dasyhelea, as key pollinators. The findings highlight the presence of these pollinators in the Yopal cocoa agroforestry system and suggest the need for further pollinator capture and identification efforts on local farms. A positive correlation was found between the number of pollinating insects and the percentage of fertilized flowers, emphasizing the crucial role of these insects in cocoa pollination and the importance of promoting their presence to optimize fruit production.